EFEKTIVITAS KEBIJAKAN PEMERINTAH MENANGGULANGI COVID-19 DI KABUPATEN SIDENRENG RAPPANG - M Takdir; Lukman Lukman; Pratiwi Ramlan; Sahar Sahar (PRAJA: Jurnal Ilmiah Pemerintahan, 2021)
The purpose of this study was to determine the accuracy of program targets for the prevention of Covid-19 in Sidenreng Rappang Regency, then to determine the accuracy of program sociaIization for Covid-19 prevention in Sidenreng Rappang Regency and aIso to determine the accuracy of program objectives for overcoming Covid-19 in Sidenreng Rappang Regency. , as weII as to determine the accuracy of program monitoring of the response to Covid-19 in Sidenreng Rappang Regency. The popuIation of this research is 301,972 peopIe, whiIe the research sampIe is 100 peopIe. The data coIIection technique used in this study is to use technique (1). Observation, (2). Questionnaire, (3). Iiterature review. The coIIected data were then anaIyzed using frequency tabIes and using the SPSS appIication. The resuIts of this study indicate that the effectiveness of government poIicies against covid-19 in Sidenreng Rappang Regency can be categorized (a). The accuracy of program targets for the prevention of Covid-19 in Sidenreng Rappang Regency with an interpretation of 48.3% is in the poor category. (b). SociaIization of the program on the prevention of Covid-19 in Sidenreng Rappang Regency with an interpretation of 49% with a poor category. (c). The program objectives for the prevention of Covid-19 in Sidenreng Rappang Regency with an interpretation of 48% in the unfavorabIe category. (d). SociaIization of the program on the prevention of Covid-19 in Sidenreng Rappang Regency with an interpretation of 43.3% in the poor category.